Foamed Bitumen Stabilised Pavements towards Western Australia Experience - Jitsangiam, Peerapong; Leek, Colin; Siripun, Komsun; Nikraz, Hamid (The Australian Geomechanical Society and New Zealand Geotechnical Society, 2012)
Foamed bitumen stabilisation is a road construction technique where hot bitumen is converted to bitumen foam by injecting a small quantity of cold water into it. It is mixed into the road pavement to bind existing or imported granular materials to produce a bound but flexible pavement with superior structural properties to the original pavement. There have been trials and research projects undertaken in Australia by Queensland Main Roads, some regional road networks in New South Wales, and City of Canning, Perth, where the process has been adopted as a preferred rehabilitation method, but these projects did not develop a complete understanding of the characteristics and performance of in-situ foamed bitumen stabilised pavements for Australian conditions. This paper reviews the results of research undertaken into the stiffness and fatigue performance of insitu foamed bitumen stabilised pavement materials at various sites in the Cities of Canning and Gosnells in Western Australia. The aim of the research was to determine if a design relationship could be developed to predict the fatigue life of insitu foamed bitumen stabilised pavements, and if the visco-elastic properties of the bitumen binder were reflected in the stiffness and fatigue performance.